Groundwater Hydraulic Characterization from Part of the Basement Area Using Vertical Electrical Sounding Data: A Case Study of Oshogbo, Southwestern Nigeria - Adeyinka, Falana Olukayode (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Groundwater potential in basement complex terrains is primarily governed by the hydraulic properties of weathered and fractured zones, as the underlying bedrock typically exhibits low porosity and permeability. This study utilized the Vertical Electrical Sounding (VES) method with a Schlumberger array at 20 locations within Oshogbo metropolis to evaluate groundwater potential. Geophysical data were processed using WINRESIST software to interpret subsurface characteristics and estimate key aquifer parameters—hydraulic conductivity, transmissivity, and longitudinal conductance—through established empirical and interpretative models. The subsurface sequence delineated includes topsoil (resistivity: 16.1–2509.8 Ωm; thickness: 0.5–9.7 m), clay (10.5–43 Ωm; 2.8–27.7 m), sandy/clayey materials (54–133 Ωm; 6–19.8 m), weathered layers (822.6–1635.7 Ωm; 6–19.8 m), and fresh bedrock (1614.1–5679.8 Ωm). Hydraulic conductivity values ranged from 0.33 to 61.36 m/day, with a mean of 20.07 m/day, while transmissivity varied in relation to both conductivity and aquifer thickness. Longitudinal conductance values ranged from 0.002 to 0.325 Ω⁻¹ (mean: 0.087 Ω⁻¹), indicating generally poor protective capacity and high vulnerability across the study area, with exceptions at Locations L01, L10, and L15, which exhibited moderate protective capacity. These three sites also demonstrated moderate hydraulic conductivity, low transmissivity, and fair groundwater potential. Overall, the integration of geoelectrical and hydrogeophysical parameters offers a reliable approach for assessing aquifer capacity and groundwater vulnerability in crystalline basement terrains.